Smaller brain volumes at two years of age in patients with hypoplastic left heart syndrome - Impact of surgical approach. (15th September 2019) - Knirsch, Walter; Heye, Kristina N.; Tuura, Ruth O'Gorman; Hahn, Andreas; Wetterling, Kristina; Latal, Beatrice; Schranz, Dietmar; Reich, Bettina
Abstract: Background: Brain growth in hypoplastic left heart syndrome (HLHS) is reduced before and after birth. Little is known about further brain growth until two years of age before Fontan procedure and the potential impact of type of surgery. Methods: In a prospective, two-center study 29 patients with HLHS and variants were treated by Norwood (n = 5) or Hybrid procedure (n = 24). At two years of age a cerebral MRI was performed and brain volumes (total gray, deep gray, white matter) and cerebrospinal fluid volume were calculated using FreeSurfer image analysis suite and compared to a healthy control group (n = 8). Results: The total brain volumes in patients with HLHS were smaller compared to controls (HLHS: 893 ± 76 ml vs. controls: 1015 ± 148 ml, p = 0.005). This difference was found in all three brain compartments after Norwood procedure, whereas patients after Hybrid procedure had total and deep gray volumes comparable to controls. When comparing Norwood to Hybrid patients, deep gray matter volume reduction was more pronounced (Norwood: 38.4 ± 4.1 ml vs. Hybrid: 44.4 ± 3.9 ml, p = 0.005) than white matter reduction (Norwood: 255 ± 19 ml vs. Hybrid: 285 ± 31 ml, p = 0.032). Conclusions: Smaller total and regional brain volumes were found two years after Norwood or Hybrid procedure in children with HLHS. The brain volume reduction was more distinct after Norwood than after Hybrid procedure. Longitudinal studies are needed to identify impact of early staged-surgeries on brain development and may become part of the decision-making process in individual patients. Highlights: At birth, brain growth in hypoplastic left heart syndrome (HLHS) is limited. At 2 years of age, total and regional brain volumes in HLHS remain smaller. The brain volume reduction is more distinct after Norwood than after Hybrid procedure. This impact of surgery may be linked with impaired neurodevelopmental outcome.